A seamless handover scheme in IPv6-based mobile networks. (10th December 2008) - Oh, Hayoung; Yoo, Kibaek; Na, Jongkeun; Kim, Chongkwon
With the rapid development of wireless technologies, the need to support moving hosts of IPv6-based mobile networks in ubiquitous is growing. Various well-known approaches to optimising the handover latency have been proposed in the literature: MIPv6, FMIPv6, HMIPv6 and F-HMIPv6. However, these approaches are inefficient in packet loss, out-of order problem, dependency of exact predictive information and a sudden disruption of the link. In this paper, we propose a seamless handover scheme with temporal reuse of Care of Addresses (CoAs) and Packet Buffering Point (PBP) in IPv6-Based mobile networks.